First post-mortem analysis of deposits collected on ITER-like components in WEST after the C3 and C4 campaigns. (28th September 2021) - Martin, Céline; Diez, Mathilde; Campos, Andrea; Cabié, Martiane; Giacometti, Gregory; Balden, Martin; Gallo, Alberto; Pegourié, Bernard; Bernard, Elodie; Tsitrone, Emmanuelle
Abstract: In order to map the complex plasma footprint observed on the lower divertor of the WEST experiment after its first phase of operation, we analysed deposits collected on ITER-like Plasma Facing Units (PFUs) exposed in the C3 (deuterium plasma) and C4 (deuterium and helium plasma) campaigns. Our results show that these deposits have multilayer structures mainly composed of tungsten, oxygen, boron and carbon, whose texture and composition vary along the radial direction. These traits allowed us to identify three types of deposits: deposits rich in boron (conditioning) in the low plasma flux area further away from the strike point, deposits rich in tungsten with traces of metallic compounds (Cu, Fe, Cr, Ni, Ag) in the high plasma flux area and deposits rich in boron and tungsten in the private flux area. In addition, we found more nanoparticles, voids and tungsten oxide layers in the deposits formed during C4 in comparison to that of C3.